AN ANALYSIS OF PROTEIN AND CALORIE CONSUMPTION IN CENTRAL JAVA - Agus Widarjono (Universitas Islam Indonesia, 2012)
AbstractThis study analyses calorie and protein consumption in Central Java Province. The calorie and protein elasticity are derived from demand elasticity of the ten food groups encompassing cereals, fish, meats, eggs and milk, vegetables, fruits, oil and fats, prepared foods and drinks, other foods and tobacco products. Most of calorie and protein-price elasticity of the ten food group are negative. Consumption of calorie and protein are most responsive to prices of eggs and milk. Protein -price elasticities are less elastic than calorie-price elasticities. Calorie and protein-income elasticity are positive and become lesselastic in moving from lower to higher income households but protein is less responsive to income change than calorie. Keywords: QUAIDS, demand elasticity, nutrient elasticity, Central Java ProvinceJEL Classification numbers: D12, O12AbstrakStudi ini menganlisis konsumsi kalori dan protein di Jawa Tengah. Elastisitas kalori dan protein dihitung dari elastisitas permintaan dari 10 kelompok komoditi makanan yang terdiri dari padi-padian, ikan, daging, telur dan susu, sayur-sayuran, buah-buahan, minyak dan lemak, makanan dan minumun jadi, makanan lainnya dan tembakau dan hasilnya. Sebagian besar elastisitas harga kalori dan protein adalah negatif. Konsumsi kalori dan protein adalah kelompok makanan yang paling responsif terhadap perubahan harga telur dan susu. Elastisitas pendapatan kalori dan protein adalah positif tetapi menjadi lebih elastis untuk rumah tangga berpenghasilan lebih tinggi tetapi protein kurang responsif terhadap perubahan pendapatan daripada kalori.Keywords: QUAIDS, elastisitas permintaan, elastisitas nutrisi, Jawa TengahJEL Classification numbers: D12, O12